2015
DOI: 10.1080/09718923.2015.11893390
|View full text |Cite
|
Sign up to set email alerts
|

A Researcher’s Dilemma: Philosophy in Crafting Dissertations and Theses

Abstract: The purpose of the present paper is to advance arguments that reflect on the researcher's dilemma caused by tendencies to conflate metatheory and paradigm in the crafting of dissertations and theses. Philosophy as an umbrella concept under which metatheory and paradigm are subsumed proves evasive in some social science dissertations and theses. Consequently, most novice researchers become confused by the conflated and unexplained use of these concepts in research. The researcher attempted to clarify philosophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 57 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Pragmatism is outcome-oriented and interested in determining the meaning of things or focusing on the product of the research (Johnson and Onwuegbuzie, 2006). Moreover, Sefotho (2015) succinctly explains that central to pragmatism is the practical nature of being, reality or phenomenon and through pragmatism, researchers become aware and are receptive of the ideas of others.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Pragmatism is outcome-oriented and interested in determining the meaning of things or focusing on the product of the research (Johnson and Onwuegbuzie, 2006). Moreover, Sefotho (2015) succinctly explains that central to pragmatism is the practical nature of being, reality or phenomenon and through pragmatism, researchers become aware and are receptive of the ideas of others.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The philosophy of this research pertains to the adoption of positivism philosophy. This is because the philosophy of positivism enabled the researcher to gather factual data through real world observations (Sefotho, 2015) and allow for the establishment of a link between management practise, employees' ability and workforce productivity. Moreover, due to the adoption of the positivism philosophy, it allowed the researcher to keep minimal interaction with the participants of the study, so that the data obtained is trustworthy and honest.…”
Section: Methodsmentioning
confidence: 99%
“…Research paradigm: According to Sefotho (2015), 'qualitative research is fundamentally phenomenological and is referred to as interpretive phenomenological research'. Hammond, Howarth and Keat (1991:1) refer to phenomenology as the 'description of things as one experiences them, or of one's experiences of things'.…”
Section: Methodology and Designmentioning
confidence: 99%
“…Phenomena are fundamentally important for qualitative researchers (Sale, Lohfeld & Brazil, 2002). They must seek understanding of people's lived experiences as phenomena for inquiry (Sefotho, 2015). Therefore, in this study, the researchers identified phenomenology as the suitable research paradigm for the study as it seeks to bring out the barriers that are encountered by physically disabled entrepreneurs in their daily lives.…”
Section: Methodology and Designmentioning
confidence: 99%